Analisis Stilistika dalam Cerpen Karena Kita Tidak Kenal Karya Farida Susanty - Hani Badiul Husna (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas PGRI Ronggolawe, 2024)
Short stories or commonly called short stories are a type of literary work that is unique. Short stories have their origins in the oral storytelling tradition that produced such well-known stories as Homer's liad and Odyssey. The purpose of this study is to analyze the stylistics or style of language used by the author in assembling his story into an interesting short story. short story